ASUHAN KEPERAWATAN KELUARGA TAHAP PERKEMBANGAN CHILD BEARING DENGAN INTERVENSI PENERAPAN JUS SEMANGKA TERHADAP PENURUNAN TEKANAN DARAH - Ely Wahyuni; Rina Puspita Sari; Hasan Basri (Nusantara Hasana Journal, 2024)
Child bearing families are families whose first child is 30 months old, this period is a transition to becoming a parent which will cause a family crisis. According to most people, this stage This is a stage full of stressors and prone to suffering from diseases, one of which is hypertension.Based on the results of the study of Mr. In Mr. Small, Mrs. S also doesn’t know how to lower high blood pressure other than taking the medicine given by the doctor. Therefore, the author is interested in applying watermelon juice to Mrs. S to lower her blood pressure. This final scientific work is to provide family nursing care at the development stage of child bearing by applying watermelon juice to reduce blood pressure. Providing watermelon juice intervention to reduce blood pressure for 7 days. Based on case studies on managed patients, it was found that giving watermelon juice had an effect on reducing blood pressure before giving watermelon juice on the first day, namely 160/90 mmHg and after giving watermelon juice on day 7, namely 120/80 mmHg.